Evaluation of transmission-blocking potential of Pv22 using clinical Plasmodium vivax infections and transgenic Plasmodium berghei - Bai J. (2023)
Antigens expressed during the sexual development of malaria parasites are transmission-blocking vaccine (TBV) targets. Pb22, a protein expressed and localized to the plasma membrane of gametes and ookinetes in Plasmodium berghei, is an excellent TBV candidate. Here, we evaluated the TB potential of the Plasmodium vivax ortholog Pv22 using a transgenic P. berghei parasite line and P. vivax clinical isolates. The full-length recombinant Pv22 (rPv22) protein was produced and used to immunize mice and rabbits to obtain antibodies. We generated a transgenic P. berghei line (TrPv22Pb) by inserting the pv22 gene into the pb22 locus and showed that Pv22 expression completely rescued the defects in male gametogenesis of the pb22 deletion parasite. Since Pv22 in the transgenic parasite showed similar expression and localization patterns to Pb22, we used the TrPv22Pb parasite as a surrogate to evaluate the TB potential of Pv22. In mosquito feeding assays, mosquitoes feeding on rPv22-immunized mice infected with TrPv22Pb parasites showed a 49.3–53.3 % reduction in the oocyst density compared to the control group. In vitro assays showed that the rPv22 immune sera significantly inhibited exflagellation and ookinete formation of the TrPv22Pb parasites. In a direct membrane feeding assay using three clinical P. vivax isolates, the rabbit anti-rPv22 antibodies also significantly decreased the oocyst density by 53.7, 30.2, and 26.2 %, respectively. This study demonstrated the feasibility of using transgenic P. berghei parasites expressing P. vivax antigens as a potential tool to evaluate TBV candidates. However, the much weaker TB activity of Pv22 obtained from two complementary assays suggest that Pv22 may not be a promising TBV candidate for P. vivax.